An Inducible Propane Monooxygenase Is Responsible for N-Nitrosodimethylamine Degradation by Rhodococcus sp. Strain RHA1 - Sharp, Jonathan O. (American Society for Microbiology (ASM), 2007)
Rhodococci are common soil heterotrophs that possess diverse functional enzymatic activities with economic and ecological significance. In this study, the correlation between gene expression and biological removal of the water contaminant N-nitrosodimethylamine (NDMA) is explored. NDMA is a hydrophilic, potent carcinogen that has gained recent notoriety due to its environmental persistence and emergence as a widespread micropollutant in the subsurface environment. In this study, we demonstrate that Rhodococcus sp. strain RHA1 can constitutively degrade NDMA and that activity toward this compound is enhanced by approximately 500-fold after growth on propane. Transcriptomic analysis of RHA1 and reverse transcriptase quantitative PCR assays demonstrate that growth on propane elicits the upregulation of gene clusters associated with (i) the oxidation of propane and (ii) the oxidation of substituted benzenes. Deletion mutagenesis of prmA, the gene encoding the large hydroxylase component of propane monooxygenase, abolished both growth on propane and removal of NDMA. These results demonstrate that propane monooxygenase is responsible for NDMA degradation by RHA1 and explain the enhanced cometabolic degradation of NDMA in the presence of propane.